Microbial Colonization in Adulthood Shapes the Intestinal Macrophage Compartment. (1st April 2019) - Schmidt, Franziska; Dahlke, Katja; Batra, Arvind; Keye, Jacqueline; Wu, Hao; Friedrich, Marie; Glauben, Rainer; Ring, Christiane; Loh, Gunnar; Schaubeck, Monika; Hackl, Hubert; Trajanoski, Zlatko; et al.
Abstract: Background and Aims: Contact with distinct microbiota early in life has been shown to educate the mucosal immune system, hence providing protection against immune-mediated diseases. However, the impact of early versus late colonization with regard to the development of the intestinal macrophage compartment has not been studied so far. Methods: Germ-free mice were colonized with specific-pathogen-free [SPF] microbiota at the age of 5 weeks. The ileal and colonic macrophage compartment were analysed by immunohistochemistry, flow cytometry, and RNA sequencing 1 and 5 weeks after colonization and in age-matched SPF mice, which had had contact with microbiota since birth. To evaluate the functional differences, dextran sulfate sodium [DSS]-induced colitis was induced, and barrier function analyses were undertaken. Results: Germ-free mice were characterized by an atrophied intestinal wall and a profoundly reduced number of ileal macrophages. Strikingly, morphological restoration of the intestine occurred within the first week after colonization. In contrast, ileal macrophages required 5 weeks for complete restoration, whereas colonic macrophages were numerically unaffected. However, following DSS exposure, the presence of microbiota was a prerequisite for colonic macrophage infiltration. One week after colonization, mild colonic inflammation was observed, paralleled by a reduced inflammatory response after DSS treatment, in comparison with SPF mice. This attenuated inflammation was paralleled by a lack of TNFα production of LPS-stimulated colonic macrophages from SPF and colonized mice, suggesting desensitization of colonized mice by the colonization itself. Conclusions: This study provides the first data indicating that after colonization of adult mice, the numeric, phenotypic, and functional restoration of the macrophage compartment requires the presence of intestinal microbiota and is time dependent.